2017
DOI: 10.1071/rd15313
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Delta-like ligand 1 alters human endometrial epithelial cell adhesive capacity

Abstract: The endometrium undergoes substantial morphological and functional changes to become receptive to embryo implantation and to enable establishment of a successful pregnancy. Reduced Delta-like ligand 1 (DLL1, Notch ligand) in the endometrium is associated with infertility. DLL1 can be cleaved by 'a disintegrin and metalloprotease' (ADAM) proteases to produce a soluble ligand that may act to inhibit Notch signalling. We used an enzyme-linked immunosorbent assay to quantify soluble DLL1 in uterine lavages from fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We have previously shown that Notch 1, DLL1 and Jagged1 are all significantly decreased in the endometrial epithelium of women with unexplained primary infertility [7,18]. Interestingly, loss of endometrial epithelial DLL1 in women with unexplained primary infertility may be due to excess cleavage of DLL1 by ADAM17, increasing soluble (s)DLL1 in the uterine lumen [59]. sDLL1 is increased in the uterine lavage of women with primary infertility and impairs blastocyst adhesion in our in vitro model of blastocyst implantation [59].…”
Section: Discussionmentioning
confidence: 65%
“…We have previously shown that Notch 1, DLL1 and Jagged1 are all significantly decreased in the endometrial epithelium of women with unexplained primary infertility [7,18]. Interestingly, loss of endometrial epithelial DLL1 in women with unexplained primary infertility may be due to excess cleavage of DLL1 by ADAM17, increasing soluble (s)DLL1 in the uterine lumen [59]. sDLL1 is increased in the uterine lavage of women with primary infertility and impairs blastocyst adhesion in our in vitro model of blastocyst implantation [59].…”
Section: Discussionmentioning
confidence: 65%
“…Greening et al (45) found a significant alteration in the intracellular protein profile and secretome of ECC-1 cells after supplementation with estrogen and progesterone compared to estrogen alone. Specifically, Van Sinderen et al (46) showed soluble delta-like ligand 1 (DLL1) was increased in the uterine lavage of infertile patients, which was associated with increased intracellular "a disintegrin and metalloprotease" protease-17 (ADAM17) expression in endometrial tissue and reduced epithelial adhesiveness of RL95 cells. ADAM17 cleaves DLL1 into its soluble form, which may inhibit Notch signaling and therefore interfere with endometrial receptivity (46)…”
Section: Resultsmentioning
confidence: 99%
“…To identify the role of specific molecules in endometrial cell adhesive capacity, the levels of the relevant factor is altered experimentally and their effect on adhesion determined. The xCELLigence technology which incorporates real-time monitoring of cell adhesion is also used as an approach to determine endometrial cell adhesive capacity (46). In this assay, endometrial epithelial cells adhesion is measured either directly on attachment to plastic plates or the plates are coated with various extracellular matrix (ECM) proteins and endometrial epithelial cell adhesion measured via electrical impedance in realtime (75).…”
Section: In Vitro Assays Used To Investigate Plasma Membrane Transformentioning
confidence: 99%
See 1 more Smart Citation
“…Staining intensity scores were determined by scorers blinded to the patient characteristics as previously published. 24 , 25 A score of 0 denoted no positive brown DROSHA or DICER staining and 3 was intense staining. Scores were averaged and plotted using Graphpad Prism 7.…”
Section: Methodsmentioning
confidence: 99%